Plasma homocysteine levels and risk of congestive heart failure or cardiomyopathy: A Mendelian randomization study - Wang, Xinyi; Chen, Zhuo; Tian, Wende; Zhang, Jie; Li, Qiuyi; Ju, Jianqing; Xu, Hao; Chen, Keji (Frontiers in Cardiovascular Medicine, 2023)
Background: Although observational studies have demonstrated associations between elevated plasma homocysteine levels and the risk of cardiovascular diseases, controversy remains. Objective: This study investigated the causal association of plasma homocysteine levels with congestive heart failure and cardiomyopathy risk. Methods: We performed a two-sample Mendelian randomization (MR) study of congestive heart failure (n = 218,792), cardiomyopathy (n = 159,811) and non-ischemic cardiomyopathy (n = 187,152). Genetic summary data on the association of single-nucleotide polymorphisms with homocysteine were extracted from the most extensive genome-wide association study of 44,147 individuals. MR analyses, including the random-effect inverse variance-weighted (IVW) meta-analysis, weighted median, simple median, maximum likelihood, penalized weighted median, MR-PRESSO and MR-Egger regression, were used to estimate the associations between the selected single-nucleotide polymorphisms and congestive heart failure or cardiomyopathy. Results: The MR analyses revealed no causal role of higher genetically predicted plasma homocysteine levels with congestive heart failure risk (random-effect IVW, odds ratio [OR] per standard deviation (SD) increase in homocysteine levels = 1.753, 95% confidence interval [CI] = 0.674 to 4.562, P = 0.250), cardiomyopathy (random-effect IVW, OR per SD increase in homocysteine levels = 0.805, 95% CI = 0.583 to 1.020, P = 0.189), or non-ischemic cardiomyopathy (random-effect IVW, OR per SD increase in homocysteine levels = 1.064, 95% CI = 0.927 to 1.222, P = 0.379). The results were consistent with other analytical methods and sensitivity analyses. Conclusions: Genetically predicted homocysteine level was not associated with congestive heart failure or cardiomyopathy risk. It is unlikely that homocysteine-lowering therapy decreases the incidence or improves the outcomes of congestive heart failure and cardiomyopathy.